2020
DOI: 10.1016/j.biopsych.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Persistently High Levels of Maternal Antenatal Inflammation Are Associated With and Mediate the Effect of Prenatal Environmental Adversities on Neurodevelopmental Delay in the Offspring

Abstract: Background: Prenatal exposure to environmental adversities, including maternal overweight/obesity, diabetes/hypertensive or mood/anxiety disorders, increases the risk for adverse neurodevelopmental outcomes in children. However, the underlying biological mechanisms remain elusive. We tested whether maternal antenatal inflammation associated with the number of neurodevelopmental delay areas in children and mediated the association between exposure to any prenatal environmental adversity and child neurodevelopme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 79 publications
1
38
0
Order By: Relevance
“…Some of the effects of maternal obesity on the offspring may be mediated by the associated increase in inflammation. Higher levels of maternal inflammation during pregnancy are associated with an increased risk of neurodevelopmental delay during childhood and mediate the effect of prenatal environmental adversity on child neurodevelopmental delay [ 35 ]. Exposure to maternal obesity during the antenatal period may result in the fetus being more susceptible to other insults such as infection or inflammation; for example, in mice, high fat diet-induced diabetes during pregnancy can potentiate the transcriptional response to a subsequent inflammatory stimulus in the fetal brain [ 36 ].…”
Section: Nutritionmentioning
confidence: 99%
“…Some of the effects of maternal obesity on the offspring may be mediated by the associated increase in inflammation. Higher levels of maternal inflammation during pregnancy are associated with an increased risk of neurodevelopmental delay during childhood and mediate the effect of prenatal environmental adversity on child neurodevelopmental delay [ 35 ]. Exposure to maternal obesity during the antenatal period may result in the fetus being more susceptible to other insults such as infection or inflammation; for example, in mice, high fat diet-induced diabetes during pregnancy can potentiate the transcriptional response to a subsequent inflammatory stimulus in the fetal brain [ 36 ].…”
Section: Nutritionmentioning
confidence: 99%
“…Studies in PREDO showed that maternal depression and/or anxiety during pregnancy were associated with increased levels of proinflammatory biomarkers high-sensitive C-reactive protein and glycoprotein throughout pregnancy [35], with morphological changes in the placenta [36], with changes in placental mRNA expression of genes regulating glucocorticoid functioning [37], and with lower epigenetic gestational age [38] and altered polyepigenetic scores of glucocorticoid-responsive genes [39] of the newborn. The increased maternal proinflammatory biomarker levels during pregnancy also predicted increased neurodevelopmental delay risk in the offspring and mediated the effects of prenatal adversity on child neurodevelopmental delay [40]. Maternal treatment with synthetic glucocorticoids during pregnancy also associated with depressive symptoms during pregnancy and predicted offspring risk of neurodevelopmental delay [41].…”
Section: Discussionmentioning
confidence: 96%
“…28 Activation of KP metabolism by stress has been associated with several proinflammatory states including depression and other neuropsychiatric disorders. 29,30 Ambient pollution may contribute to such proinflammatory states with higher incidence and severity of COVID-19, by two mechanisms: (1) The atmosphere, rich of air pollutants, may promote a longer permanence of the of viral particles in the air. 31 (2) The exposure to polycyclic aromatic hydrocarbons (PAHs), that may induce impaired immune function and low-grade inflammation, thereby promoting a higher incidence and severity of the cytokine storm triggered by viral infections.…”
Section: Mechanism Of Melatonin Actionsmentioning
confidence: 99%
“…64 Whether prenatal stress induces FGR or not, the effect of prenatal environmental adversity on child neurodevelopmental delay seems to be mediated by higher levels of maternal inflammation, especially when persisting throughout pregnancy. 30 Consequently, several clinical studies are ongoing to ameliorate outcomes in FGR using high oral doses of melatonin. 64…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%